Identifying novel inhibitor of quorum sensing transcriptional regulator (SdiA) of Klebsiella pneumoniae through modelling, docking and molecular dynamics simulation. Issue 10 (13th June 2021) - Ahmed, Mohammad Z.; Muteeb, Ghazala; Khan, Saif; Alqahtani, Ali S.; Somvanshi, Pallavi; Alqahtani, Mohammed S.; Ameta, Keshav Lalit; Haque, Shafiul
Abstract: In this study, attempts have been made to identify novel inhibitor(s) of SdiA (a homolog of LuxR transcription regulator) of Klebseilla pneumoniae using various computational techniques. 4LFU was used as a template to model the structure of SdiA. ProCheck, Verify3D, Ramachandran plot scores and ProSA-Web confirmed the good quality of the model as the root mean square deviation (RMSD) between SdiA model, and 4LFU template was estimated to be 0.21 Å. The secondary structural contents of SdiA model were predicted using PDBsum. The only binding site of SdiA was identified (area = 523.083 Å 2 and volume = 351.044 Å 3 ) using CASTp. Molecular docking at three different levels [high throughput virtual screening, standard-precision (SP) and extra-precision (XP) dockings] with increasingly stringent conditions was performed using Glide on Selleck's express pick library (L3600). A total of 61 ligands were found to bind with high affinities to the active site of SdiA. Further, the effect of solvent on protein-ligand interaction was evaluated by performing molecular mechanics-general born surface area (Prime/MM-GBSA). On the basis of Prime/MM-GBSA score, molecular dynamics simulation (50 ns) was performed on the ligand (WAY-390139-A) showing lowest binding energy to confirm the stability of protein-ligand complex. Docking energy and the corresponding binding affinity of WAY-390139-A towards SdiA were estimated to be –13.005 kcal mol –1 and 3.46 × 10 9 M −1, respectively. Our results confirm that WAY-390139-A binds at the autoinducer binding site of SdiA with high affinity and stability and can be further exploited as potential drug against K. pneumoniae after experimental validation. Communicated by Ramaswamy H. Sarma Graphical Abstract: